The Kuznets curve versus cycles: Rethinking the determination and long-run evolution of income distribution - Thomas Palley (Hans-Böckler-Stiftung, Macroeconomic Policy Institute (IMK), Forum for Macroeconomics and Macroeconomic Policies (FMM), 2025)
This paper presents a theory and model of long-run cycles in income inequality. The model explains the historical pattern of income distribution identified by Kuznets (1955) and Piketty (2014). It breaks with conventional marginal product theory which claims functional income distribution is determined by the technological conditions of production. Instead, it emphasizes the role of socio-political forces that shape and drive fluctuations in the level of popular political organizations, which then impact distribution. That impact includes assessment and attribution of productivity contributions. The model provides a framework for interpreting the historical evolution of income distribution and inequality, and for reflecting on current conditions and possible future developments. The core message is twofold. First, socio-political developments matter for income distribution. Second, if those developments are cyclical, income distribution will also exhibit cyclicality.
Keywords: E3; J3; N3; 330; Income distribution; inequality; cycles; Kuznets curve; Piketty